Peningkatan Kemampuan Berpikir Tingkat Tinggi Siswa Melalui Pembelajaran Matematika Berbantuan LKPD Berbasis HOTS - Lucy Asri Purwasi; Nur Fitiyana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to find out the improvement of students' high level of thinking ability through hots-based LKPD rocky mathematics learning. This research is a kuantitafif research with research design one group pretest -posttest design. This research instrument is a question of essays totaling 3 questions consisting of indicators of tingi level thinking, namely analyzing, evaluating and creating. The sample selection was done in cluster random sampling with the selected sample is class VIII-2 which consists of 22 students. The data obtained were analyzed using unilateral t-tests. Based on the results of data analysis at a significant level of α = 0.05 obtained ρ value 0.033 with an average high level of thinking ability of students in grade VIII SMP Negeri 5 Lubuklinggau city is 74.09 with a good category. In conclusion, there is a significant increase in students' high-level thinking ability after doing LKPD-assisted mathematics lessons based on HOTS. Keywords: High Level Thinking, HOTS Based LKPD, Mathematics